Challenging perceptions about men, women, and forest product use: a global comparative study - Sunderland, Terry C.H.; Achdiawan, R.; Angelsen, A.; Babigumira, R.; Ickowitz, A.; Paumgarten, F.; Reyes García, Victoria; Shively, G.E. (Elsevier, 2014)
This study uses a multi-case dataset to question current assumptions about the gender differentiation of forest product use. We test some of the commonly held ideas on how men and women access, manage, and use different forest products. Overall, we found significant gender differentiation in the collection of forest products, which seems to support the claim that there are distinctive "male" and "female" roles associated with the collection of forest products. However, we also found that men play a much more important and diverse role in the contribution of forest products to rural livelihoods than previously reported, with strong differences across tropical Asia, Africa, and Latin America.